1996
DOI: 10.1016/s0960-9822(02)70786-0
|View full text |Cite
|
Sign up to set email alerts
|

Faciogenital dysplasia protein (FGD1) and Vav, two related proteins required for normal embryonic development, are upstream regulators of Rho GTPases

Abstract: We conclude that FGD1 and Vav are regulators of the Rho GTPase family. Along with their target proteins Cdc42, Rac and Rho, FGD1 and Vav control essential signals required during embryonic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 201 publications
(206 citation statements)
references
References 33 publications
12
192
1
1
Order By: Relevance
“…This began with the localization of both FGD1 and Cdc42 at the Golgi membranes (Erickson et al, 1996;Estrada et al, 2001), and we have shown here that a loss of the activities of either FGD1 or Cdc42 results in similar aberrant transport phenotypes. Furthermore, FGD1 inhibitors affect both Cdc42 activity (Olson et al, 1996) and Cdc42 binding to the Golgi complex (see Figure 6). Given that Cdc42 can be activated by many different GEFs (Hoffman and Cerione, 2002), why are none of these able to efficiently substitute for FGD1 in the support of post-Golgi transport?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This began with the localization of both FGD1 and Cdc42 at the Golgi membranes (Erickson et al, 1996;Estrada et al, 2001), and we have shown here that a loss of the activities of either FGD1 or Cdc42 results in similar aberrant transport phenotypes. Furthermore, FGD1 inhibitors affect both Cdc42 activity (Olson et al, 1996) and Cdc42 binding to the Golgi complex (see Figure 6). Given that Cdc42 can be activated by many different GEFs (Hoffman and Cerione, 2002), why are none of these able to efficiently substitute for FGD1 in the support of post-Golgi transport?…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, the GFP-FGD1-AS mutant comprises nearly full-length Fgd1 cDNA that encodes a naturally occurring FGDY-related alternative FGD1 transcript that lacks 36 amino acids in exon 6. This alters the FGD1 DH domain and generates a dominant-negative FGD1 protein that cannot activate Cdc42 (Olson et al, 1996). In contrast, the GFP-FGD1-dbdel fusion construct contains deletions of residues 146-188 and thus removes N-terminal inhibition and results in a constitutively active form of FGD1.…”
Section: Fgd1 Deficit Inhibits Constitutive Post-golgi Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…As we identified a functional role of ERM proteins in the local recruitment and activation of Cdc42, we were interested to test the role of ERM proteins in modulating GEF activity and behavior. We analyzed the morphological changes in MDA-MB-231 cells after overexpression of a panel of GEFs: the Cdc42-specific Rho GEF FGD1 and the Cdc42/Rho-specific GEF onco-Dbl (Olson et al, 1996); the Rac-specific GEF Tiam1 (constitutively activated by an N-terminal deletion; Michiels et al, 1997); and the Rho-specific GEF p190RhoGEF (van Horck et al, 2001). Expression of FGD1 in MDA-MB-231 cells induces formation of filopodia and membrane ruffles ( Figure 6A, top panel left).…”
Section: N-ermad(e244k) Disrupts the Morphological Reorganization Indmentioning
confidence: 99%
“…14, April 2003 1627 Gavin et al, 2001). Because many DH domains show exchange activity on multiple Rho GTPase family members (Hart et al, 1994;Olson et al, 1996), we tested DH domain specificity using recombinant GST fusion proteins in several complementary assays. Figure 2A displays the intersectin 1L domain structure and aa position of the recombinant fusion proteins used in this study.…”
Section: Intersectin 1l Gef Inhibitory Mechanismmentioning
confidence: 99%